Strengthening the Network of High Conservation Value Forests in Boreal Landscapes - Mikusiński, Grzegorz; Orlikowska, Ewa H.; Bubnicki, Jakub W.; Jonsson, Bengt Gunnar; Svensson, Johan (Frontiers in Ecology and Evolution, 2021)
The natural and old-growth forests and their associated biodiversity continues to fade worldwide due to anthropogenic impact in various forms. The boreal forests in Fennoscandia have been subject to intensive clearfelling-based forestry since the middle of 20th century. As a result, only a fraction of forests with long temporal continuity remains at the landscape level. In Sweden, some of these primary forests have been formally protected, whereas others that have also been identified as having conservation value, are located outside the protected area network. Collectively, both protected and not protected known valuable primary forests are included in a nationally delineated network of high conservation value forests (HCVF). In addition to HCVF, older forests that have not been clearfelled since the mid-1900s, i.e. “proxy continuity forests”, have recently been mapped across the entire boreal biome in Sweden. In this paper, we analyze how these proxy continuity forests may strengthen the HCVF-network from a green infrastructure perspective. First, we evaluated the spatial overlap between proxy continuity forests and HCVF. Second, we performed a large-scale connectivity analysis, where we showed that adding proxy continuity forests located outside HCVF strongly increases the structural connectivity of protected-forest network. Finally, by assessing habitat suitability for virtual species specialized in pine, spruce and broadleaf forests, we found large regional differences in the ability to secure habitat and thereby functional green infrastructure by considering currently unprotected primary forest with high conservation value. We show that by protecting those forests, the area of habitat for low demanding species dependent on spruce or pine forests can be largely increased. For high demanding species additional habitat restoration in the landscape matrix is needed. By contrast, even counting all valuable broadleaf forests available, is not enough to provide suitable habitat for their associated species, which indicates a large need for landscape-scale habitat restoration initiatives in particular for broadleaf forests.